Evaluasi Kualitas Fisik dan Uji Palatabilitas Ransum Berbasis Rumput Kumpai Tembaga (Hymenachne acutigluma) Melalui Kombinasi Lumpur Sawit dan Daun Ubi Kayu - Riswandi Riswandi; Basuni Hamzah; Agus Wijaya; Arfan Abrar; M. Reski Valian Akbar (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Riswandi et al, 2018. Physical Quality Evaluation and Palatability of (Hymenachne acutigluma) through Combination of Palm Oil and Cassava Leaves. JLSO 7(2):204-212. The aim of this study to investigate the physical quality and palatability based feed Hymenachne acutigluma which is combine cassava leaves and palm oil as animal feed. This reseach was done in 3 months in Cattle Nutrition and Feed Laboratory and Livestock Experiment Studies Program Faculty of Agriculture, University of Sriwijaya. This reseach used completely randomazed design method with 4 treatments and 4 replications. The treatment consisted of R0 (85% Hymenachne acutigluma + 15% concretate), R1 (55% Hymenachne acutigluma + 30% cassava leaves + 15% concrentate), R2 (55% Hymenachne acutigluma + 30% palm oil + 15% concentrate), R3 (55% Hymenachne acutigluma + 15% cassava leaves + 15% palm oil + 15% concentrate). The observed variabels are smell, water ration, density and palatability of feed consisted. The results showed thet the treatment had significant effect (P<0.05) on density of the ration and had no significant effect (P>0.05) on the smell and the water content of the feed. The result of the palatability rations show thet the treatment of R1 is the most favored by the livestock. The conclusion of this reseach is indicate that the combination 55% Hymenachne acutigluma + 30% cassava leaves + 15% concrentate can improve the physical quality and palatability.